Tumor associated macrophages reprogrammed by targeted bifunctional bioorthogonal nanozymes for enhanced tumor immunotherapy. (June 2022) - Wei, Yue; Wu, Si; Liu, Zhenqi; Niu, Jingsheng; Zhou, Ya; Ren, Jinsong; Qu, Xiaogang
Graphical abstract: Herein, a bifunctional bioorthogonal nanozyme targeting M2 macrophages was designed to induce macrophages polarization and intratumoral oxidative damage for enhanced tumor synergistic immunotherapy. Importantly, the nanozyme could catalyze the in-situ synthesis of histone deacetylase inhibitor (HDACi) vorinostat to achieve local M2 re-education, while effectively avoiding unnecessary inflammation in normal tissues, thus puting forward a more biocompatible and effective way for TAMs repolarization. Abstract: Cancer immunotherapy has emerged as a promising cancer treatment. However, its efficacy is often limited by the immunosuppressive tumor microenvironment (TME) in solid tumors. Herein, a new strategy has been presented by using bioorthogonal chemistry to reprogram TME. We designed a bifunctional mannose (Man) vector decorated palladium bioorthogonal nanozyme for in-situ synthesis of histone deacetylase inhibitor (HDACi) vorinostat (FDA approved) with the ability to remodel tumor microenvironment. To the best of our knowledge, this is the first report to use a bioorthogonal nanozyme for cancer immunotherapy. In particular, the nanozyme could preferentially accumulate in M2 macrophages (termed M2Φ) to achieve local M2 re-education, which effectively avoided unnecessary inflammation in normal tissues. Moreover, vorinostat-induced TME reprogramming was synergistic with peroxidase-like activity of the nanozyme, and achieved enhanced tumor synergistic immunotherapy. In colon cancer (CT26)-tumor-bearing BALB/c mice, the nanozyme demonstrated macrophages polarization targeting M2Φ and activation of innate immune system, resulting in significantly enhanced tumor growth inhibition. Our work not only provides a new effective way to reprogram TME in vivo, but also shed light on the design of novel bioorthogonal nanozymes for cancer immunotherapy.